2014
DOI: 10.1016/j.powtec.2014.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of gases in powder solid matrices and their applications: A review

Abstract: Gas encapsulation in solid matrices can be an important means to sequester harmful or greenhouse gases and to store useful gases for their subsequent release for a targeted application. In this review, recent developments, the characteristics and gas adsorption capacity of non-organic and organic solid powder matrices (e.g. activated carbons, carbon nanotubes, zeolites, metal-organic frameworks, and cyclodextrins); and potential applications of their complexes in various fields (energy, environment protection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 246 publications
(267 reference statements)
0
45
0
2
Order By: Relevance
“…From quantification of the CO 2 isosteric heat of adsorption, the nature of the CO 2 adsorption can be determined, where low heat of adsorption (8-41 kJ mol -1 ) revealed physisorption and higher value of heat of adsorption (62-418 kJ mol -1 ) indicated chemisorption. Furthermore, this parameter showed that the CO 2 interaction with the adsorbent material might be mainly an intermolecular force or hydrogen bond (Ho et al 2014;Zhao et al 2012).…”
Section: Heat Of Co 2 Adsorption Of the Adsorbentsmentioning
confidence: 99%
See 4 more Smart Citations
“…From quantification of the CO 2 isosteric heat of adsorption, the nature of the CO 2 adsorption can be determined, where low heat of adsorption (8-41 kJ mol -1 ) revealed physisorption and higher value of heat of adsorption (62-418 kJ mol -1 ) indicated chemisorption. Furthermore, this parameter showed that the CO 2 interaction with the adsorbent material might be mainly an intermolecular force or hydrogen bond (Ho et al 2014;Zhao et al 2012).…”
Section: Heat Of Co 2 Adsorption Of the Adsorbentsmentioning
confidence: 99%
“…Based on the nature of interactions, adsorption can be classified into two types: (1) physical adsorption and (2) chemical adsorption. In physical adsorption, the molecules are physisorbed because of physical forces (dipoledipole, electrostatic, apolar, hydrophobic associations or Van der Waals) where the bond energy is 8-41 kcal mol -1 , while in chemical adsorption, molecules chemisorbed (chemical bond; covalent, ionic or metallic) and the bond energy is about 60-418 kcal mol -1 (Ho et al 2014). The adsorbent sample used in physisorption can be regenerated by simple degassing method.…”
Section: Adsorptionmentioning
confidence: 99%
See 3 more Smart Citations